Development of humic acid and alginate-based wound dressing and evaluation on inflammation - Yalman, Volkan; Lacin, Nelisa Turkoglu (TAYLOR & FRANCIS LTD, 2019)
The excessive collagen type I accumulation in the extracellular matrix leads to scar formation. We aimed to develop a biomaterial for scarless tissue regeneration by suppressing collagen type I overexpression, and stimulation of collagen type III expression. Alginate (Alg) is a widely used natural material for biomedical applications, and humic acid (HA) is a natural macromolecule with antioxidant, anti-inflammatory properties. Humic acid and the alginate were cross-linked to obtain a hydrogel membrane. The cell viability of the Humic Acid-Alginate (HA-Alg) hydrogel on L929, HaCaT, macrophage cells were determined. The biodegradation tests revealed that 76% of the HA-Alg hydrogel mass was lost at four weeks The effect of HA-Alg hydrogel on TNF alpha level observed as 1212.50 +/- 98.63 pg/mL. HA-Alg suppressed collagen type I overexpression, which has a significant role in scar formation and stimulated collagen type III expression, which has a vital role in wound healing.
Keywords: Alginate; Humic Acid; Hydrogel; Biodegradable; Wound Dressing; Scarless; IN-VITRO; HYDROGELS; REPAIR; CYTOTOXICITY; BIOCOMPATIBILITY; BIODEGRADATION; CHITOSAN; Materials Science